2021
DOI: 10.7759/cureus.19139
|View full text |Cite
|
Sign up to set email alerts
|

Nottingham Hip Fracture Score: Does It Predict Mortality in Distal Femoral Fracture Patients?

Abstract: Background Patients with distal femur fractures are associated with mortality rates comparable to neck of femur fractures. Identifying high-risk patients is crucial in terms of orthogeriatric input, pre-operative medical optimisation and risk stratification for anaesthetics. The Nottingham Hip Fracture Score (NHFS) is a validated predictor of 30-day mortality in neck of femur fracture patients. In this study, we aim to investigate and evaluate the suitability of the NHFS in predicting 30-day as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Previous studies have also reported that increased NHFS is closely related to prolonged hospitalization stay 14 . The NHFS contains many components that can reflect poor physical condition, including advanced age, low hemoglobin level, cognitive impairment, complications, and the demand for other people's care before surgery 15 . All the above components can affect the recovery of these patients after surgery and increase the risk of complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also reported that increased NHFS is closely related to prolonged hospitalization stay 14 . The NHFS contains many components that can reflect poor physical condition, including advanced age, low hemoglobin level, cognitive impairment, complications, and the demand for other people's care before surgery 15 . All the above components can affect the recovery of these patients after surgery and increase the risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…14 The NHFS contains many components that can reflect poor physical condition, including advanced age, low hemoglobin level, cognitive impairment, complications, and the demand for other people's care before surgery. 15 All the above components can affect the recovery of these patients after surgery and increase the risk of complications. The postoperative complications could significantly influence the length of hospitalization.…”
Section: Clinical Significance Of Preoperative Assessmentmentioning
confidence: 99%
“…It has shown correlation with CFS in predicting outcomes within the hip fracture population 25 and value in predicting outcome in distal femoral fractures. 26 However, as this score is not routinely collected in those without hip fractures, it has not been included in our analysis. Given our results have demonstrated similar outcomes between those with and without hip fractures, further work should be undertaken to compare CFS and NHFS as predictors of outcomes in fragility fractures outside of the hip fracture population.…”
Section: Discussionmentioning
confidence: 99%
“…We noted that the 30-day survival in low NHFS group patients was slightly lower than in the high NHFS group, but this did not reach statistical significance due to the overlap of confidence intervals. Previous studies performed with a much larger patient cohort have shown that the 30-day survival was indeed higher in patients with lower NHFS (with a score below 5) in patients who sustained a hip fracture or other femoral fractures [ 6 , 19 , 20 ]. For one-year mortality, our study did show a higher survival rate in patients with NHFS of less than 5, and these results were statistically significant, which was consistent with previously reported findings [ 7 ].…”
Section: Discussionmentioning
confidence: 99%